PERCEPTIONS OF PARENTS, STUDENTS, AND TEACHERS ON ONLINE LEARNING DURING COVID-19: EVIDENCE FROM A DEVELOPING COUNTRY PERSPECTIVE - Dr. Nasir Gul; Arfa Khan; Danyal Sikandri; Muhammad Sadiq (Spectrum of Engineering Sciences, 2025)
This study investigates the challenges and opportunities associated with online learning from the perspectives of 300 students, 200 teachers, and 100 parents from colleges and higher education institutions (HEIs) in the southern zone offering undergraduate and master's programs. Conducted during the COVID-19 pandemic, the research highlights several key issues, including technical difficulties, lack of engagement, distractions at home, inadequate support, and difficulties in understanding materials. These challenges frequently disrupted the online learning experience, with technical issues and the absence of face-to-face interaction being notably detrimental. Barriers such as poor internet access and limited device availability further exacerbated the situation. Despite these challenges, significant opportunities for improvement were identified. Teachers emphasized the need for more resources for creating multimedia-rich learning materials and regular professional development. Students highlighted the importance of clearer course materials, practical applications, and reliable access to digital resources. Parents stressed the need for accessible teachers, timely feedback, and better communication from institutions. Recommendations for enhancing online learning include establishing comprehensive technical support, improving instructional design, fostering better engagement through live sessions and peer collaboration, and enhancing communication channels between institutions and parents. Addressing these recommendations can significantly improve the quality of online education, creating a more effective and enjoyable learning experience for all stakeholders involved.